Low-Volatility Anomaly in the U.S. Stock Markets 1975 - 2019 - Aho, Sami (My University, 2022)
This Master’s thesis focuses on the risk-adjusted performance of low-volatility strategies. This thesis examines if the previously documented anomaly is still present and if the strategy compensates the investor with above-market risk-adjusted returns. Since the low-volatility effect is an umbrella term used by the financial literature, this thesis focuses specifically on the trailing low-volatility and trailing low-beta strategies. Previous literature has found that using these relatively simple risk measures to sort portfolios compensates investors with larger returns and lower risk. Such a risk-return relationship makes the strategy especially compelling for investors. A positive relationship between risk and return is a central paradigm in finance. However, the findings of the low-volatility studies show that such a relationship is not observed empirically. Instead, the relationship is flat or even reversed in some cases. While many anomalies have been documented, the low-volatility anomaly’s direct implication to the financial theory makes the anomaly even more fascinating. Earlier studies have found that it does not matter what volatility-related risk measure is used; the results indicate that the investor is compensated with higher returns for lower risk. Since low-volatility strategies are complex to form and upkeep, the strategy is more directed to professional investors with access to ample data storage and computing power. The strategy requires substantial capital and is subject to transaction costs as portfolios are balanced monthly. While multiple studies have argued that the transaction costs for a low-volatility strategy are insignificant, they are still large compared to a buy-and-hold strategy that many non-professionals use. Therefore, the strategy works only on a large scale. A retail investor that wishes to gain access to a low-volatility strategy should seek out low-volatility funds or ETFs instead of trying to mimic the portfolios themselves. The thesis differs from the prior studies by using newer data and three-factor and five-factor models that earlier studies have not used. Additionally, the CAP-model is also used to determine whether earlier findings can be replicated. Furthermore, previous studies lack necessary robustness tests implemented in this thesis. This thesis finds that the low-volatility and low-beta strategies generate significant alpha in U.S. stocks from 1975 to 2019 when the CAPM or Fama-French three-factor model is used. Furthermore, the alpha disappears when the newer Fama-French five-factor model is used. The results show that these returns are generated with a much lower standard deviation indicating a reversed risk-return relationship. The main conclusion is that the low-volatility anomaly exists in the US stocks, but the profitability and investment factor can largely explain it.

Tutkielman tarkoitus on tutkia alhaisen volatiliteetin strategioiden riskikorjattua suorituskykyä. Aikaisemmat tutkimukset ovat löytäneet, että alhaisen volatiliteetin strategioiden riskikorjattu suorituskyky on erinomainen. Tutkielma pyrkii löytämään vastauksen voiko aiempien tutkimuksien havainnot vahvistaa uudemmalla osake aineistolla sekä kaikkein uusimmilla osakehinnoittelu malleilla. Alhaisen volatiliteetin strategia on sateenvarjo termi, jota käytetään akateemisessa rahoituksessa. Tämän tutkielman keskiössä on kaksi alhaisen volatiliteetin strategiaa: pieni volatiliteetti ja pieni beta. Aikaisemmat tutkimukset ovat todenneet, että käyttämällä näitä yksinkertaisia tapoja alhaisen volatiliteetin mittaamiseen ja portfolioiden rakentamiseen, sijoittajat ovat voineet saada korkeampia tuottoja alhaisemmalla riskillä. Tämä alhaisen riskin ja korkean tuoton välinen suhde tekee strategiasta erityisen mielenkiintoisen kaikille sijoittajille. Rahoitusteorian mukaan riskin ja tuoton pitäisi olla positiivisesti korreloituneita. Aikaisemmat alhaisen volatiliteetin tutkimukset ovat kuitenkin osoittaneet, ettei senkaltaista suhdetta voida empiirisesti vahvistaa. Sen sijaan nämä aiemmat tutkimukset ovat löytäneet, että riskin ja tuoton suhde on pikemminkin tasainen tai jopa käänteinen. Vaikka monet tutkimukset muista strategioista ovat tehneet saman löydöksen, alhaisen volatiliteetin strategian suora implikaatio riskin ja tuoton väliseen tasaiseen tai negatiiviseen suhteeseen tekee strategiasta erittäin mielenkiintoisen. Lisäksi aikaisempi kirjallisuus alhaisen volatiliteetin strategioista on osoittanut, että käytettäessä mitä tahansa volatiliteetti liitännäistä riski mittaria sijoittaja voi odottaa korkeampia tuottoja matalammalla riskitasolla. Volatiliteetti liitännäiset strategiat ovat monimutkaisia rakentaa ja ylläpitää. Lisäksi strategian toimeenpano vaatii merkittävän määrän pääomaa sekä sen transaktiokulut ovat suuret suhteessa osta-ja-pidä-strategiaan. Näin ollen strategiaa voi suositella ainoastaan ammattilaissijoittajille, joilla on kokemusta kvantitatiivisten strategioiden rakentamisesta. Tästä johtuen strategia toimii ainoastaan suuressa mittakaavassa, käyttäen merkittäviä määriä osakkeita jokaisessa portfoliossa. Tavanomaisen sijoittajan, joka haluaa päästä osaksi strategiaa, kannattaa etsiä strategiaan erikoistunut osakerahasto tai ETF-rahasto ja sijoittaa sen kautta strategiaan. Tämä tutkielma osoittaa, että alhaisen volatiliteetin strategioiden avulla voidaan saavuttaa positiivisiä riskikorjattuja tuottoja Yhdysvaltain osakemarkkinoilla. Lisäksi tutkimus osoittaa, että nämä tuotot saavutetaan alhaisemmalla tuottojen keskihajaumalla implikoiden käänteistä riskin ja tuoton suhdetta. Alhaisen volatiliteetin strategian kannattavuutta selittää pääosin tuotto- ja investointi-faktorit.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance